THE INFLUENCE OF WORK ENGAGEMENT AND EMPLOYEE RELATIONSHIP ON EMPLOYEE WELL-BEING AT PT. REMAJA JAYA MOBILINDO MANADO - Wajong, Frity C.; Pangemanan, Sifrid S.; Saerang, Regina T. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: In Manado, there are several Honda dealers. One of them is Honda Martadinata which is now run by PT. Remaja Jaya Mobilindo Manado. High levels of work engagement are when employees are involved with, committed to, enthusiastic, and passionate about their work. Employee relationship is one of key factors that can increase the employeeâ€™s well-being. The purpose of this study is to know the influence of work engagement and employee relationship on employee well-being at PT. Remaja Jaya Mobilindo Manado. This research using multiple regression with total sample 101 employees. The result shows that both of work engagement and employee relationship have a significant and positive influence toward employee well-being. The employee feel engage with their work and put all their efforts and knowledge on it and also has a great communication between one and another employee and also with their superiors. The company should arranging their employee to put them into a fitted division according to their skills and talent so their employee can give an efficient work that can increase the company performance in all sectors and should work hand-in-hand to enhance workplace happiness and in generating productive employee with the potential of being high performance achievers.Â Keywords: employee well-being, work engagement, employee relationship